8 - LE DEVELOPPEMENT DU CAPITALISME AGRAIRE ET L'EMERGENCE DE PETITS PLANTEURS A L'ILE MAURICE - Raj VIRAHSAWMY, (Africa Development, 1979)
The development of agrarian capitalism and the emergence of small plan ters in Mauritius. The whole historical process of Mauritius has been a series of tran sition towards capitalism. For historical reasons, it has by-passed a pre capitalist mode of production, the primitive accumulation of capital and even laissez-faire capitalism. From a slave-labour mercantilist relay at the periphery of the Dutch and French mercantilist system, it was trans formed, under British occupation, into a slave-labour sugar plantation economy. After the abolition of slave-labour and its replacement by immigrant indentured labour from India, the plantation economy under went a semi-capitalist transformation, but retaining many vestiges of slavery. Concentration of land and capital has been a constant theme during the whole period. The rise of small planter-class is but a conse quence of the concentration of capital itself. Access to marginal land left over from the process of concentration of better land liberated labour, confined previously to plantation «camps». It also gave birth to villages and created a semi-proletariat who could be «free» labour and small planters at the same time. This process, beginning at the turn of this century, consolidated agrarian capitalism and stimulated further concentration of capital, reaching today, the supreme stage of monopoly capitalism. Sugar capital has been transformed into financial capital which now dominates all the key sectors of the economy. However, it is a dominated monopoly capitalism at the periphery, whose accumulation of capital is dependent upon the international division of labour.